1989
DOI: 10.1093/jac/23.5.773
|View full text |Cite
|
Sign up to set email alerts
|

A multicentric study of netilmicin once daily versus thrice daily in patients with appendicitis and other intra-abdominal infections

Abstract: This multicentric, randomized, double-blind trial compared the efficacy and safety of netilmicin, 4.5 mg/kg od and 1.5 mg/kg tid, in patients with intra-abdominal infections. Of 114 patients enrolled, 57 patients (mean age 40.3 years) in the od group and 55 (mean age 36.8 years) in the tid group were evaluated for efficacy; 58 and 56 patients in corresponding groups were evaluated for safety. Among those evaluated for efficacy were 12 od-treated and 11 tid-treated patients with documented septicaemia, and 32 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 0 publications
1
43
1
Order By: Relevance
“…In a large meta-analysis of patients with any type of gram-negative infection, this regimen was shown to be of equal efficacy compared to divided daily dose regimens, and possibly associated with fewer side effects [73]. Two prospective trials also found that once daily administration of aminoglycosides was efficacious in patients with intra-abdominal infections [74,75].…”
Section: Recommended Antimicrobial Regimensmentioning
confidence: 99%
“…In a large meta-analysis of patients with any type of gram-negative infection, this regimen was shown to be of equal efficacy compared to divided daily dose regimens, and possibly associated with fewer side effects [73]. Two prospective trials also found that once daily administration of aminoglycosides was efficacious in patients with intra-abdominal infections [74,75].…”
Section: Recommended Antimicrobial Regimensmentioning
confidence: 99%
“…45 In the most detailed data regarding microbiologic efficacy, 56 patients with documented bacterial infection received amikacin once/day either alone or in combination with another antibiotic. 52 Six classifications of infections were pneumonia (16 patients); chronic otitis (7); meningitis, bacteremia, septicemia (9); osteomyelitis (12); pyelonephritis (7); and peritonitis (5 …”
Section: Microbiologic Efficacymentioning
confidence: 99%
“…However, data from in-vitro and experimental in-vivo studies suggest that once-daily dosing of aminoglycoside might be at least as efficacious and potentially less toxic (Frame et al, 1977;Blaser, Stone & Zinner, 1985a;Gerber et al, 1989;Mattie, Craig & Pechere, 1989). Single-daily dosing of aminoglycosides has also been studied clinically (Powell et al, 1983;Hollender et al, 1989). However, a large number of patients need to be evaluated in comparative studies to detect clinically significant differences in either efficacy or toxicity.…”
Section: Introductionmentioning
confidence: 99%